Critical Review of Life Cycle Assessment of Local and Imported Food Commodities - Doffannoel Claudio Sihotang; Edberd E. Leopard; I Dewa Made Adi Kresna; Iqbal Zahid Abdullah Haris; Nurhayati (Jurnal Komputer, Informasi dan Teknologi, 2026)
This study aims to critically reviews Life Cycle Assessment (LCA) research in Indonesia’s food sector, focusing on both locally produced and imported commodities. Employing a critical review methodology, peer-reviewed articles and international reports published were analyzed for compliance with ISO 14040/44, data transparency, system boundary definitions, and methodological gaps. The results reveal substantial variability in environmental impacts: local rice and soybean value chains exhibit high methane emissions and fertilizer-related effects, whereas imported wheat, soybean, and beef accrue larger carbon footprints due to long-distance transport. Moreover, most studies adopt a cradle-to-gate scope with limited sensitivity or uncertainty analyses, which undermines result robustness. We conclude that standardizing LCA protocols, expanding primary data collection, and incorporating cradle-to-grave scopes and uncertainty analyses are vital to enhance the reliability of LCA for Indonesia’s sustainable food policy